Attitudes Towards Sexuality in Song of Songs and in the Corpus Paulinum: A Comparison - van der Merwe, Dirk Gysbert (Journal for Semitics, 2017)
<span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-ZA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Throughout history Song of Songs has been read and interpreted from various perspectives. Popular and academic Jewish and Christian publications allegorise and metaphorise the meaning of the words and images in Song of Songs. The focus of this research is on a literary-didactic reading as proposed by Turner, which seems to be the most obvious interpretation of Song of Songs. The research on the sexuality perspective communicated in the Song is then compared with the Pauline attitude to sex and marriage in order to find out whether Paul’s attitude to sex differs from or corresponds with what we find in Song of Songs. The corpus Paulinum and Song of Songs should both be read with their cultural contexts in mind. While Song of Songs focuses on the erotic love between two lovers, the corpus Paulinum focuses on sexual immorality